Rebel poet : (continuing the oral tradition) : more stories from a 21st century Indian - Clark, Louis V., III (Wisconsin Historical Society Press, 2019)
"This eagerly anticipated follow-up to the breakout memoir How to Be an Indian in the 21st Century delves more deeply into the themes of family, community, grief, and the struggle to make a place in the world when your very identity is considered suspect. In Rebel Poet: More Stories from a 21st Century Indian, author Louis Clark examines the effects of his mother's alcoholism and his young sister's death, offers an intimate recounting of the backlash he faced as an Indian on the job, and celebrates the hard-fought sense of home he and his wife have created. Rebel Poet continues the author's tradition of seamlessly mixing poetry and prose, and is at turns darker and more nuanced than its predecessor"--